2016
DOI: 10.1080/15622975.2016.1224924
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disturbances and upregulation of brain arousal during daytime in depressed versus non-depressed elderly subjects

Abstract: The data confirm the hypothesis that in persons with depressive syndromes sleep disturbances are related to upregulation of brain arousal the next day. This finding is in line with the concept that dysregulation of brain arousal is a central pathophysiological aspect in depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 38 publications
5
27
0
Order By: Relevance
“…According to the Arousal Regulation Model of Affective Disorders [7,8], hypostable and hyperstable levels of arousal contribute to manic and depressive-like behavior, respectively. Several empirical studies have supported this model [9][10][11][12]. Notably, similar concepts have previously been proposed on the relationship between arousal and the personality traits extraversion [13] and sensation seeking [14].…”
Section: Introductionsupporting
confidence: 71%
“…According to the Arousal Regulation Model of Affective Disorders [7,8], hypostable and hyperstable levels of arousal contribute to manic and depressive-like behavior, respectively. Several empirical studies have supported this model [9][10][11][12]. Notably, similar concepts have previously been proposed on the relationship between arousal and the personality traits extraversion [13] and sensation seeking [14].…”
Section: Introductionsupporting
confidence: 71%
“…Thus, we hypothesize that adulthood insecure attachment positively predicts an individual's sleep quality. Sleep problem has been proved to impair college students' mental and physical health, and sleep disorders can cause depression-like behaviors [20]. Thus, we hypothesize that sleep problem mediates the relationship between adulthood insecure attachment and depression (H1) ( Figure 1).…”
Section: Introductionmentioning
confidence: 97%
“…In many cases disturbed sleep emerges even before the onset of clinical depression, up to 90% of people with depression complain about diminished sleep quality, which often includes self-referential, agonizing rumination while being awake during the night (German: "Nächtliches Grübeln") (Benjamins et al, 2017;Nolen-Hoeksema, Wisco, & Lyubomirsky, 2008). At the same time, this reduced sleep quality is associated with altered state of vigilance regulation during daytime-in particular hyperarousal (Riemann et al, 2010;Ulke et al, 2017). Also, many antidepressants decrease vigilance (Alberti, Chiesa, Andrisano, & Serretti, 2015;Hensch et al, 2015)-in addition to their effect on frontal functional connectivity (see above)-and it has been suggested that this effect on vigilance contributes to their antidepressant effects (Hegerl & Hensch, 2014).…”
Section: Introductionmentioning
confidence: 99%